2008
DOI: 10.1124/dmd.107.019687
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cytochrome P450 Protein Expression along the Entire Length of the Intestine of Male and Female Rats

Abstract: ABSTRACT:Intestinal cytochrome P450 (P450) proteins play an important role in the biotransformation of drugs and may significantly limit their oral absorption and bioavailability. Therefore, we have investigated the amount of P450 proteins via Western blot analysis along the entire intestine of male and female rats. Despite of the use of an inbred rat strain, controlled housing conditions for the animals, and a timed sample preparation, high interindividual differences in the expression of all P450 proteins wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 34 publications
(42 reference statements)
2
47
2
Order By: Relevance
“…Several P450s are expressed in the rat intestine. Although general patterns of expression of P450s along the intestinal tract have been recognized in the rat, the intra-and interindividual variation of P450 protein expression is also remarkable (Lindell et al, 2003;Mitschke et al, 2008). A recent study in brain capillaries (Bauer et al, 2004) showed a very rapid up-regulation of Pgp upon exposure to ligands of the orphan receptor, pregnane X receptor, which initiates a signaling cascade of Pgp expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several P450s are expressed in the rat intestine. Although general patterns of expression of P450s along the intestinal tract have been recognized in the rat, the intra-and interindividual variation of P450 protein expression is also remarkable (Lindell et al, 2003;Mitschke et al, 2008). A recent study in brain capillaries (Bauer et al, 2004) showed a very rapid up-regulation of Pgp upon exposure to ligands of the orphan receptor, pregnane X receptor, which initiates a signaling cascade of Pgp expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, modeling of intestinal first-pass metabolism is difficult because of physiological complexities unique to the intestine. Several reports have suggested that animals and humans have much in common with regard to intestinal physiological conditions (Cao et al, 2006;Hurst et al, 2007;Nishimura et al, 2007;Mitschke et al, 2008). Accordingly, we tried to predict intestinal first-pass metabolism in humans by our model using monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The protein levels of CYP3A1 and CYP3A2 in liver and intestine were evaluated using Western blot, as described previously (Kim et al, 2005a). Intestinal (duodenal and jejunal) homogenate was prepared by a method described previously (Mitschke et al, 2008). Proteins (20 g) of hepatic microsomal or intestinal homogenate were resolved by SDS-polyacrylamide (10%) gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%